Certainty of the Death Penalty in Terrorism Crimes from the Perspective of International Criminal Law - Satria Bintang, Angga; Helvis, Helvis (Ann Publisher, 2024)
Terrorism is an extraordinary crime which is classified as a crime against humanity (Crime Against Humanity), and is a serious threat to the supervision of every country because terrorism is an international crime which poses a danger to security, world peace and is detrimental to the welfare of society. It needs to be eradicated systematically. planned and sustainable so that the human rights of many people can be protected and upheld. The aim of this research is to find out the certainty of the Death Penalty in Terrorism crimes from an International Criminal Law Perspective and to find out regarding Human Rights to the certainty of the Death Penalty in Terrorism Crimes from an International Criminal Law Perspective. Data collection in legal writing is library research (library research). The debate regarding the death penalty is also related to the right to life which in international legal instruments and in the 1945 Constitution is included in the category of rights that cannot be reduced under any circumstances (non-derogable rights). The practice of capital punishment in Indonesia is still considered class biased and discriminatory. because in both the Criminal Code and the ICCPR the death penalty is permitted for the most serious types of crimes, including the crime of terrorism.